Type 3 Fimbriae and Biofilm Formation Are Regulated by the Transcriptional Regulators MrkHI in Klebsiella pneumoniae - Johnson, Jeremiah G. (American Society for Microbiology, 2011)
Klebsiella pneumoniae is an opportunistic pathogen which frequently causes hospital-acquired urinary and respiratory tract infections. K. pneumoniae may establish these infections in vivo following adherence, using the type 3 fimbriae, to indwelling devices coated with extracellular matrix components. Using a colony immunoblot screen, we identified transposon insertion mutants which were deficient for type 3 fimbrial surface production. One of these mutants possessed a transposon insertion within a gene, designated mrkI, encoding a putative transcriptional regulator. A site-directed mutant of this gene was constructed and shown to be deficient for fimbrial surface expression under aerobic conditions. MrkI mutants have a significantly decreased ability to form biofilms on both abiotic and extracellular matrix-coated surfaces. This gene was found to be cotranscribed with a gene predicted to encode a PilZ domain-containing protein, designated MrkH. This protein was found to bind cyclic-di-GMP (c-di-GMP) and regulate type 3 fimbrial expression.